The influence of progesterone and 17β-estradiol on the activity of peripheral blood mononuclear cells - Sikora, Justyna; Mielczarek-Palacz, Aleksandra; Kondera-Anasz, Zdzisława; Kulińska, Justyna (Menopause Review/Przegląd Menopauzalny, 2011)
Objective: Sex hormones can affect the activity of immune cells, particularly lymphocytes and monocytes. The aim of the study was to investigate the activity of peripheral blood mononuclear cells (PBMC) after stimulation of progesterone and 17β-estradiol. The indicator of PBMC activity was the concentration of transforming growth factor-β (TGF-β) produced by those cells. It is an important factor involved in the regulation and course of the menstrual cycle and implantation Materials and methods: Material for the study comprised peripheral blood mononuclear cells isolated from the blood of 10 donors. The resulting cells were cultured for 48 h in the medium and in medium supplemented with different concentrations (1 ng/ml and 5 ng/ml and 10 ng/ml), progesterone and 17β-estradiol. Concentration of TGF-β in the supernatant of PBMC culture was determined by ELISA immunoassay. Results: The analysis of results showed that after stimulation of both progesterone and 17β-estradiol, the secretory activity of PBMC was changed. With increasing concentrations of progesterone, the concentration of TGF-β2 was significantly higher as compared to unstimulated cultures (p < 0.0001). In contrast, significantly increased secretion of the parameter by PBMC was observed after stimulation of cells of 17β-estradiol at a concentration of 5 ng/ml (p < 0.0001). Conclusions: Progesterone and 17β-estradiol have effects on PBMC activity. Increased activity of these cells is observed after stimulation of higher levels of hormones, which greatly influences the secretion of TGF-β.